Screening for eating disorders, dysfunctional exercise, and menstrual dysfunction in female athletes - Fernandez-del-Valle, M.; Quesnel, D. A.; Mitchell, J. J.; Robert-McComb, J. J. (The active female. Health issues throughout the lifespan, 2023)
While exercise is viewed as a positive part of a healthy lifestyle, various health issues may arise throughout the life of a female athlete. Issues may be related to dissatisfaction with athletic performance, overuse injuries including bone stress fractures, and/or specific medical issues. No health issues should be viewed in isolation, but rather in the holistic context of the individual. Understanding the interrelated entities of energy availability, menstrual function, and bone mineral density as a portion of the female athlete triad is essential to the care of the active female. Energy availability can be negatively impacted by inadequate intake of nutrition through disordered eating (inadvertent or purposeful) or one of the pathologic eating disorders, and/or abnormally increased training volume, viewed as dysfunctional exercise. Low energy availability can then negatively impact hormones related to metabolism and menstrual function, ultimately impacting bone health. Regular menstrual cycles have been viewed, by some, as a vital sign for the female athlete`s overall health and energy availability. Irregular menses or amenorrhea should be thoroughly evaluated. Abnormal menses is frequently found to be related to inadequate energy availability and resultant diminished sex hormones, known as functional hypothalamic amenorrhea, a diagnosis of exclusion. This also causes changes in bone health and puts the athlete at risk for stress fractures, suboptimal peak bone mass density, and possible future osteoporosis. In order to heighten awareness regarding the need to screen for potentially harmful conditions in the female athlete, this chapter provides guidance regarding screening for eating disorders, dysfunctional exercise, and menstrual dysfunction. By understanding methods to screen for these entities, those providing care and supervision to female athletes can be empowered to assist the active female to maintain a healthy relationship with exercise throughout the course of her lifetime.